Mechanical and microstructural characterization of powder metallurgy CoCrNi medium entropy alloy - Moravcik, Igor; Cizek, Jan; Kovacova, Zuzana; Nejezchlebova, Jitka; Kitzmantel, Michael; Neubauer, Erich; Kubena, Ivo; Hornik, Vit; Dlouhy, Ivo (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2017)
The present study is focused on synthesis and mechanical properties characterization of equiatomic CoCrNi medium entropy alloy (MEA). Powder metallurgy processes of mechanical alloying (MA) with subsequent spark plasma sintering (SPS) for bulk alloy densification have been utilized. As opposed to the single-phase alloys of identical composition fabricated via casting routes, the alloy after SPS compaction consisted of a major FCC solid solution phase (94.4%), minor fraction of secondary BCC phase (5.6%, precipitated at the FCC grains boundaries), and negligible amount of oxide inclusions. The alloy exhibited high ultimate tensile strength of 1024MPa and a elongation to fracture of 26%. Elastic modulus of the alloy reached 222GPa and the thermal expansion coefficient (CTE) was measured as 17.4 × 10−6K−1 The plastic deformation in the alloy is carried out by a combination of dislocation glide and mechanical nano-twinning at room temperature.